Symboliczno-teologiczna wymowa chrześcijańskiego ołtarza w kontekście przeobrażeń jego formy i umiejscowienia, w świetle dokumentów Kościoła, pism Patres Ecclesiae i współczesnych badań. - Tejszerska, Anna (TECHNE. Seria Nowa, 2018)
Over the centuries, the Christian altar, where the Eucharistis performed and which invariably constitutes the heart and the focal point of the liturgic congregation, has undergone numerous transformations. They ought to be interpreted through the key of accentuating various dimensions of Eucharistic spirituality, fathoming the essence of the sacrament and the care for its worthy celebration, including the changing artistic and cultural tendencies, and searching for the forms that serve the purposes of the apostolic mission of the Church. The abundance of symbolism attributed to the altar and its theological grounds is by no means inferior to the variety of ‘altar forms reflecting not only the motives of human imagination, but also the principles stemming from a clear comprehension of the mystery’(Ecclesia de Eucharistia 50). The purpose of the article is to trace back the transformations of the form and shape of the Lord’s Table and its artistic decoration, in the context of the symbolic and theological tenor of the altar in reference to the transformations of the Eucharist spirituality, in view of studies on the history of art and the Church, liturgical regulations and Church documentation. The paper focuses mainly upon the central altar within the Roman Catholic Church, with the richness of forms and shapes of its artistic decoration. Timewise, it includes the whole history of the development of the cult of Christianity, emphasising both the changeability and continuity of the transformations within the liturgic sphere, and a permanent and yet variably expressed altarocentrism